Ride-Hailing to Rail in the Suburbs: Can Subsidized Rides Enhance First and Last Mile Access for the Carless? - Hue-Tam Jamme; Andrew Eisenlohr; Deepak Bahl; Tridib Banerjee (Findings)
The study examines whether GoMonrovia, a public-private partnership between Lyft and the City of Monrovia, provides an effective and equitable first-last mile solution in a suburban setting. Datasets were obtained from Lyft, the American Community Survey, and an online survey. With more than half-a-million rides per year before COVID-19, the program proved to be an attractive mobility option. A large majority (77%) of respondents used GoMonrovia to or from the Monrovia Gold Line Metro station. Significant predictors of first-last mile use of subsidized Lyft rides include not having access to a car and living beyond walking distance from the station.